IMPLEMENTASI PERTANIAN CERDAS IKLIM UNTUK MENINGKATKAN PRODUKTIVITAS TEBU DI INDONESIA / Implementation of Climate-Smart Agriculture to Boost Sugarcane Productivity in Indonesia - Rivandi Pranandita Putra; Nindya Arini; Muhammad Rasyid Ridla Ranomahera (Jurnal Penelitian dan Pengembangan Pertanian, 2021)
Sugar is one of Indonesia’s strategic commodities, but its production fluctuates over time and is still unable to comply with the national sugar demand. This condition may even get worst with climate change. Although climate-smart agriculture is a promising thing, it is basically a genuine concept for many farmers in Indonesia, including sugarcane growers. The paper briefly reviews and argues agronomic practices as a climate-smart agriculture approach adapted by sugarcane growers in Indonesia to increase its production under the changing climate. Some agronomic practices can be adopted by the Indonesian sugarcane growers as climate-smart agriculture, i.e., efficient irrigation, improved drainage of sugarcane plantations, the use of suitable sugarcane cultivars, green cane harvesting-trash blanketing, the amendment of soil organic matter, crop diversification, precision agriculture, and integrated pest management. From the Indonesian government’s side, research should be propped as there is limited information about the effectiveness of each aforementioned agronomic intervention to alleviating the adverse effect of climate change and to improving sugarcane growth. Practically, to ensure the success of climate-smart agriculture implementation in the Indonesian sugar industry, multistakeholders, i.e., sugarcane growers, researchers, civil society, and policymakers, should be involved, and the government needs to link these stakeholders.Keywords: Sugarcane, productivity, climate-smart agriculture, agronomic management, precision agriculture AbstrakGula merupakan salah satu komoditas strategis Indonesia, namun produksinya mengalami fluktuasi dan belum dapat memenuhi kebutuhan gula nasional. Kondisi ini diperburuk oleh perubahan iklim. Pertanian cerdas iklim memberikan peluang besar bagi tanaman tebu untuk dapat beradaptasi dan memitigasi dampak perubahan iklim. Meskipun pertanian cerdas iklim menjanjikan, namun merupakan hal baru bagi banyak petani di Indonesia, termasuk petani tebu. Tulisan ini menelaah dan mengemukakan praktek agronomi sebagai pendekatan pertanian cerdas iklim yang dapat diterapkan petani tebu di Indonesia dengan tujuan meningkatkan produksi tebu di bawah kondisi perubahan iklim. Terdapat beberapa praktik agronomis sebagai bagian dari pertanian cerdas iklim yang dapat diadopsi petani tebu di Indonesia, seperti efisiensi irigasi, perbaikan sistem drainase, pemilihan kultivar tebu yang sesuai, pemanfaatan residu serasah tebu, peningkatan bahan organik tanah, diversifikasi tanaman, pertanian presisi, dan pengelolaan hama terpadu. Dari perspektif pemerintah Indonesia, penelitian harus didukung karena terbatasnya informasi efektivitas masing-masing intervensi agronomi tersebut untuk mengurangi dampak buruk perubahan iklim dan untuk meningkatkan pertumbuhan tebu. Secara praktis, untuk memastikan keberhasilan penerapan pertanian cerdas iklim pada industri gula Indonesia, multi-stakeholder yang terdiri atas petani tebu, peneliti, masyarakat sipil, dan pembuat kebijakan harus saling terlibat dan pemerintah perlu menghubungkan para pemangku kepentingan ini.Kata kunci: Tebu, produktivitas, pertanian cerdas iklim, manajemen agronomis, pertanian presisi